Keseimbangan Mikrobiota Usus dengan Resistensi Insulin pada Pasien Obesitas: Literatur Review Tahun 2016–2024 - Aura Mulya Ramadhani; Aryanti R. Bamahry; Sudirman Katu (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Obesity is a growing global health issue affecting both developed and developing countries. Despite various preventive efforts, the prevalence of obesity continues to rise. One of the emerging approaches in managing obesity and its complications is by modulating gut microbiota balance. Gut microbiota plays a significant role in energy metabolism, inflammation regulation, and insulin sensitivity. An imbalance in gut microbiota, known as dysbiosis, is frequently observed in obese individuals and has been associated with increased insulin resistance, a key feature of type 2 diabetes mellitus. This study aims to systematically review the relationship between gut microbiota imbalance and insulin resistance in obese patients, based on literature from 2016 to 2024. The literature search was conducted through accredited databases such as PubMed, Google Scholar, and others using the keywords “Gut Microbes,” “Insulin Resistance,” and “Obesity.” From 500 initial articles, 10 highly relevant journals were selected for further analysis. The review findings reveal a strong association between dysbiosis and increased insulin resistance through various mechanisms, including short-chain fatty acid (SCFA) production, activation of inflammatory pathways, and disruption of glucose metabolism. Several studies also suggest that interventions such as probiotics, prebiotics, and fecal microbiota transplantation may improve insulin sensitivity. However, more longitudinal and interventional studies are needed to establish a strong causal relationship. These findings highlight the importance of maintaining gut microbiota balance as a potential strategy in managing obesity and insulin resistance.